Design of CDI (Capasitive Discharge Ignition) and Motor Spark Plugs Test Kits - Alamur Rosidil Wafa; Akhmad Ahfas (Universitas Muhammadiyah Sidoarjo, 2021)
The Ignition on a motorcycle is an electrical system that produces sparks in the combustion chamber. If there is a mass of ferromagnetic material moving closer to the sensor, then the pulser will generate an electric current. Greater the electric current it generates. With the working principle of such a pulser, it can be used as a rotation sensor and sent to the ignition coil to produce a higher voltage which will produce sparks at the end of the spark plug electrode. The perfection of the system affects the motor work system. A good CDI condition will make it easier to increase the RPM (Rotations Per Minute) and when the spark plugs are in good condition, the motorbike's performance is getting optimal. There can be a useful tool for analyzing the damage to the CDI and the spark on the spark plug by integrating the electronic system in the motor ignition system. An electronic circuit that connects the motorcycle's ignition system through the output of the pulser circuit signal, which triggers the CDI input instead of the pulse magnet. Because the CDI and motor spark plugs are one of the main components that play an important role in the performance of the combustion motor. So that the electrical system can work without using mechanics and can be used as a tool to be able to analyze CDI damage and motor spark plug performance because CDI and spark plugs are some of the main components that play an important role in combustion motor performance. The result is that the tool can test CDI and motor spark plugs efficiently after which it can conclude the damage and can distinguish the characteristics of the CDI and the motor plugs.